Meningkatkan Kemampuan Pelafalan Siswa Dengan Menggunakan Metode Mall (Mobile-Assissted Language Learning) - Endang Sulistyowati (Peneliti.net, 2021)
MALL method is a part of M-Learning whereas the flexibility of its technology that can be used everywhere and more personal can be a new way in conducting learning process, emphasizing on its continuity or accessing the context beyond directly. Classroom action research is used as the research method. Participants in this research were 11th grade students of one of senior high school in West Java. Interview, obervation report, quesionnaire and students’ score on pre-test and post-test used as the instruments in collecting the data. Further, these data analyzed by quantitative and qualitative method. Result showed that MALL method is able to improve the students pronunciation abilities, eventhough the researcher faced many difficulties in the process of applying it.